The Effect of Corporate Governance Mechanisms, Capital Structure and Firm Size on Risk Management Disclosure - Larasati, Desi; Asrori, Asrori (Accounting Analysis Journal, 2020)
This study aims to determine the effect of the duties and responsibilities of directors, institutional ownership, managerial ownership, capital structure and firm size on RMD in an Islamic banks. The population in this study is the Islamic Banks in Indonesia. There is 35 annual reports of Islamic banks as samples. The analytical method used is multiple linear regression analysis using SPSS tool. The results showed that the firm size significant positive effect on RMD. While the other variables are the duties and responsibilities of directors, institutional ownership, managerial ownership and capital structure does not affect the RMD. Researchers further advised to analyze other factors that may affect the RMD on Islamic banks such as the duties and responsibilities of the board of commissioners. Keywords: Risk Management Disclosure (RMD), Mechanism Corporate Governance, Duties and Responsibilities of Directors, Institution Ownership, Management Ownership, Capital Structure, Firm Size.